The Influence of AI Personalization, Perceived Usefulness, and Trust in Technology on Online Purchase Intention - Franciscus Dwikotjo Sri Sumantyo; Titin Jumriah; Noorhayani Dyani Laksmi (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the influence of AI personalization, perceived usefulness, and trust in technology on online purchase intention in the context of e-commerce. The rapid advancement of artificial intelligence has enabled online platforms to deliver personalized experiences, which are expected to enhance consumer engagement and purchasing behavior. This research adopts a quantitative approach using a cross-sectional survey design. Data were collected from 200 respondents who have experience in online shopping and exposure to AI-based personalization features. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to evaluate both the measurement and structural models. The results indicate that AI personalization, perceived usefulness, and trust in technology all have a significant positive effect on online purchase intention. Among these variables, trust in technology emerges as the most influential factor, highlighting the importance of security, reliability, and consumer confidence in digital transactions. AI personalization also plays a crucial role by enhancing the relevance of product recommendations and improving user experience, while perceived usefulness contributes by increasing the efficiency and convenience of online shopping. The model demonstrates strong explanatory power, indicating that these variables collectively provide a comprehensive understanding of consumer behavior in digital marketplaces. The findings of this study offer both theoretical and practical implications, suggesting that e-commerce businesses should focus on integrating advanced AI technologies with trust-building strategies and user-friendly systems to increase consumer purchase intention.